Association between methylenetetrahydrofolate reductase tagging polymorphisms and susceptibility of hepatocellular carcinoma: a case–control study. Issue 11 (12th November 2019) - Zhang, Sheng; Lin, Jing; Jiang, Jiakai; Chen, Yu; Tang, Weifeng; Liu, Longgen
Abstract: Polymorphisms in one-carbon metabolism genes may influence the susceptibility to hepatocellular carcinoma (HCC). In the present study, we studied methylenetetrahydrofolate reductase ( MTHFR ) tagging polymorphisms in 584 HCC cases and 923 controls. Polymerase chain reaction was harnessed to detect MTHFR genotype. Overall, our results showed that genotype distribution of MTHFR rs4846048 and rs4845882 polymorphisms was not different between HCC patients and controls. MTHFR rs9651118 and rs1801133 loci were protective factors for HCC (rs9651118: CT vs. TT: adjusted odds ratio (OR) = 0.67, 95% confidence interval (CI): 0.49–0.90, P =0.008 and TC/CC vs. TT: adjusted OR = 0.70, 95% CI: 0.53–0.93, P =0.015; rs1801133: GA vs. GG: adjusted OR = 0.72, 95% CI: 0.54–0.97, P =0.031, AA/GA vs. GG: adjusted OR = 0.76, 95% CI: 0.57–0.99, P =0.045). However, MTHFR rs3753584 locus was a candidate for susceptibility to HCC (CT vs. TT: adjusted OR = 1.67, 95% CI: 1.20–2.32, P =0.003 and TC/CC vs. TT: adjusted OR = 1.59, 95% CI: 1.15–2.20, P =0.005). Results of haplotype analysis suggested that MTHFR Grs1801133 Trs3753584 Grs4845882 Ars4846048 Trs9651118 was associated with the risk of HCC (OR = 1.55, 95% CI: 1.16–2.07, P = 0.003). The power of our study also confirmed these associations (the value of power >0.80). In summary, our findings suggested that MTHFR rs3753584, rs9651118 and rs1801133 polymorphisms may affect the risk of HCC in Chinese Han population. In future, our findings should be further validated in additional case–control studies.